2012
DOI: 10.4103/0257-7941.103193
|View full text |Cite
|
Sign up to set email alerts
|

Skin rash on site of application of Dashanga Lepa (polyherbal formulation): A rare and unexpected drug reaction

Abstract: Dashanga Lepa is a polyherbal preparation of Ayurveda, used to treat many skin ailments and rheumatoid arthritis. However, its toxicological property has not been reported so far. We report a rare case of cutaneous adverse reaction in the form of skin rash following the application of Dashanga Lepa. A 42-year-old female patient with a Pittakaphalaprakruthi (constitution) developed skin rashes, soon after the application of Dashanga Lepa over the applied area, which disappeared after stopping the suspected drug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 2 publications
(2 reference statements)
0
4
0
Order By: Relevance
“…This may be a good example for unpredictable or idiosyncratic reaction because it is very hard to predict cause and effect relation in modern pharmacology or Ayurvedic pharmacology as has been reported in the case of administration of Daśāṅga lepa induced skin rashes[ 7 ] so it may be grouped under type-B type of ADR.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This may be a good example for unpredictable or idiosyncratic reaction because it is very hard to predict cause and effect relation in modern pharmacology or Ayurvedic pharmacology as has been reported in the case of administration of Daśāṅga lepa induced skin rashes[ 7 ] so it may be grouped under type-B type of ADR.…”
Section: Discussionmentioning
confidence: 99%
“…Such as manifestation of skin diseases on external administration of juice of Bhallātaka ( Semecarpus anacardium ),[ 4 ] by suppressing the urge of Chardi (vomiting),[ 5 ] Vamana mithyayoga (inadequate administration of emesis). [ 6 ] There are few recently published ADR reports on Ayurvedic drugs as Daśāṅga lepa (poly-herbal formulation) induced skin rashes[ 7 ] and thyroiditis, followed by ginger consumption. [ 8 ]…”
Section: Introductionmentioning
confidence: 99%
“…Adverse events reported in relation to herbal products are frequently attributable either to poor quality or to improper use, and it is therefore difficult to distinguish genuine adverse reactions to herbal medicines and herbal products until the cause of such events has been identified (6). There are handfuls of case reports where specific cutaneous adverse effects are documented to be caused by Ayurveda medicines (7,8,9). Till date, the diagnosis of cutaneous adverse drug reactions is purely clinical.…”
Section: Introductionmentioning
confidence: 99%
“…However, there is paucity in adverse drug reaction (ADR) reporting for herbal or ayurvedic drugs to pharmacovigilance authorities. Few studies published have shown that serious adverse reactions may happen due to herbal medicines [2,3,4,5,6]. Ashwagandha (Withania somnifera) is an ayurvedic medicine possesses anti-inflammatory, anti-tumor, anti-stress, antioxidant, immunomodulatory, hemopoietic, and rejuvenating properties [7].…”
Section: Introductionmentioning
confidence: 99%